The Portuguese Recognition of Prior Learning (RPL) policy agenda - examining a volatile panacea by means of ethno-phenomenological interpretations - Rosanna Barros (University of Bologna, 2014)
This article discusses some results of a qualitative policy research study whose principal aims were: i) to analyse how sustainable the top-down decisions made on recognition of prior learning (RPL) policies and processes are; ii) to underline some of the local achievements of Portugal's new public policies on adult experiential learning, in operation since the Lisbon Agenda. The analytical policy models proposed by Lima and Guimarães (2011) were used for studying the various educational rationales involved. An ethno-phenomenological approach has been bringing to the fore the perceptions of educational actors, as: i) the weakness of the adult education public offer provision; ii) the vulnerable status of professionals working in the national scene. And a major strength of the experiential approach to learning: it's potential to create opportunities for applying skills to new situations that can be related to education for a sustainable future, as UNESCO urges.